The Integrated Study on the Chemical Profiling to Explore the Constituents and Mechanism of Traditional Chinese Medicine Preparation Huatuo Jiuxin Pills Based on UPLC-Q-TOF/MSE and Network Pharmacology - Zhu, Yulong; Zhu, Yaqin; Tao, Shuyue; Liang, Wanhui; Zhang, Jing; Zhang, Yunjing; Xuan, Zihua; Xu, Jingjing; Peng, Can; Wu, Huan; Wu, Deling (Frontiers in Molecular Biosciences, 2022)
Huatuo Jiuxin Pills (HJP), a traditional Chinese medicine (TCM) preparation, has been widely used to treat cardiovascular diseases (CVDs) for more than 20 years. However, there were still gaps in the study of chemical components and potential pharmacological effects in the HJP. In this study, ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF/MSE) combined with network pharmacology was used to comprehensively explore the chemical components in HJP and explore its potential active compounds and the mechanism for the treatment of CVDs. A total of 117 compounds, mainly including saponins, cholic acids, and bufadienolides, were rapidly identified and characterized. Simultaneously, the fragmentation mode and characteristic ion analysis of different types of representative compounds were carried out. Network pharmacology results showed that the more important active ingredients mainly include 5β-hydroxybufotalin, 19-oxo-cinobufagin, bufarenogin, etc. While, the main targets were PIK3CA, MAPK1, VEGFA and so on. Importantly, HJP has therapeutic effects on CVDs by acting on endocrine resistance, PI3K-Akt signaling pathway, HIF-1 signaling pathway, etc. In addition, molecular docking results showed that the core active ingredients with higher degrees in HJP have a strong affinity with the core targets of CVDs. The current work fills the gap in the chemical substance basis of HJP, and also facilitates a better understanding of the effective components, therapeutic targets, and signaling pathways of HJP in the treatment of CVDs.